Labour supply and employment in the euro area countries - developments and challenges - Klaus Masuch; Ramon Gómez-Salvador; Nadine Leiner-Killinger; Rolf Strauch; Jarkko Turunen; Melanie Ward-Warmedinger; Jan De Mulder; Harald Stahl; Yvonne McCarthy; Daphne Nicolitsas; Aitor Lacuesta; Mathilde Ravanel; et al. (European Central Bank (ECB), 2008)
The aim of this report, which has been prepared by a Task Force of the Monetary Policy Committee of the Eurosystem, is to describe and analyse the main developments in labour supply and its determinants in the euro area, review the links between labour supply and labour market institutions, assess how well labour supply reflects the demand for labour in the euro area and identify the future challenges for policy-makers. The data available for this report generally cover the period from 1983 to spring 2007.
Keywords: E5; J1; J2; J6; 330; Labour supply; employment; participation; hours worked; immigration; skill and education; structural policies; labour demand; unemployment; euro area countries; labour markets; taxes and benefits; childcare; pensions; training; human capital; labour quality; working time and contracts; discrimination; mismatch; returns to education.; Arbeitsangebot; Arbeitsmarkt; Arbeitsnachfrage; Arbeitsverwaltung; Allokationseffizienz; EU-Staaten